Improving the performance of bituminous mixtures (cover layer) using fiberglass - ترخان, سامر; بسام سلطان (Latakia University Journal -Engineering Sciences Series, 2024)
Roads are exposed to many problems and defects, such as alligator cracks, reflection, rutting, and deformations resulting from high traffic loads and weather factors. Therefore, these problems cannot be addressed by improving the performance of bituminous pavements to increase the materials’ resistance to fatigue and improve their durability. Adding fiberglass is one of the important methods used to improve the performance of bituminous pavements. Bituminous paving, determining the volumetric properties of the reference bituminous mixture, and carrying out laboratory experiments according to the Marshall method using bitumen of grade (60-70). The results showed that the ideal bitumen percentage is 4.2% of the total weight of the bituminous mixture, and five percentages of glass fibers were chosen to study their effect on the properties. The modified bitumen mixture and its comparison with the reference mixture, which is respectively( 0.6 - 0.5 - 0.4 - 0.3 - 0.2)% Of the total weight of the bitumen mixture, the results showed that the ideal addition percentage of glass fibers is 0.33% of the total weight of the mixture, at which the bituminous paving shows better performance and higher resistance to stresses, loads, weather factors, and high temperatures, as the addition of fibers contributes to improving the properties of the bitumen mixture. In accordance with the required local technical conditions and specifications.